Analysis of the spatiotemporal changes in terrestrial water storage anomaly and impacting factors over the typical mountains in China. Issue 2 (17th January 2018) - Yang, Peng; Zhan, Chesheng; Xia, Jun; Han, Jian; Hu, Shi
ABSTRACT: Based on the terrestrial water storage anomaly (TWSA) from Gravity Recovery and Climate Experiment (GRACE) and Global Land Data Assimilation System, Tropical Rainfall Measuring Mission products, groundwater level data, and teleconnection indexes, combined with the Mann–Kendall test, the spatiotemporal distribution of TWSA and its potential drivers during 2002–2015 were explored over the mountains areas located in the transitional zone between the non-monsoon and monsoon areas in China. The major conclusions can be seen the follows: (1) as for the time series of TWSA from GRACE, the increasing trend with the rate of 0.15 mm month −1 was investigated over Karst area, and the decreasing trends with the rate of −0.61 and −0.32 mm month −1 were exhibited over Taihang Mountains and Hengduan Mountains; (2) the significant decreasing trend ( p  < 0.05) of TWSA from GRACE was found over Taihang Mountains and the west of Hengduan Mountains, and the significant increasing trend ( p  < 0.05) was explored over the north of Karst area; (3) precipitation played an important role in the changes of TWSA over Hengduan Mountains and Karst area, while the groundwater played a dominant role in the changes of TWSA over Taihang Mountains. The anthropogenic contributions of −92.9 ± 22.3, 13.47 ± 3.2, and 61.9 ± 14.85 mm yr −1 to TWS were detected over the Taihang Mountains, Hengduan Mountains, and Karst area, respectively. In addition, El Niño-Southern Oscillation (ENSO) impacted on the changes of TWSA deeply over these three regions, especially the Hengduan Mountains and Karst area during 2002–2015.